2022
DOI: 10.3390/biomedicines10092205
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Immunotherapy in Poorly Differentiated Sinonasal Tumors

Abstract: The sinonasal cavities harbor a wide variety of rare cancer types. Histopathological classification can be challenging, especially for poorly differentiated tumors. Despite advances in surgery and radio-chemotherapy, the 5-year survival rate is still very low. Thus, there is an unmet clinical need for new therapeutic options. We retrospectively evaluated poorly differentiated tumors of 9 different histological subtypes from 69 patients who had received conventional treatments for the presence of CD8+ tumor-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
0
6
0
1
Order By: Relevance
“…Moreover, several studies on tumor-infiltrating lymphocytes and aspects of the PD-L1/PD1 checkpoint have indicated a role for immunotherapy in several sinonasal tumor subtypes. [60][61][62] Limited information is available regarding the effectiveness and ad hoc use of targeted agents for treating SNCs. In a multicenter, retrospective study in Japanese patients with recurrent or metastatic head and neck cancer who received nivolumab for the first time between July and December 2017, overall, 256 patients were enrolled in this study.…”
Section: Adjuvant Immunotherapy and Other Biologic Response Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several studies on tumor-infiltrating lymphocytes and aspects of the PD-L1/PD1 checkpoint have indicated a role for immunotherapy in several sinonasal tumor subtypes. [60][61][62] Limited information is available regarding the effectiveness and ad hoc use of targeted agents for treating SNCs. In a multicenter, retrospective study in Japanese patients with recurrent or metastatic head and neck cancer who received nivolumab for the first time between July and December 2017, overall, 256 patients were enrolled in this study.…”
Section: Adjuvant Immunotherapy and Other Biologic Response Modifiersmentioning
confidence: 99%
“…Candidate therapies include PI3K/mTOR inhibitors for intestinal‐type adenocarcinomas, EGFR and CDK4/6 inhibitors for SCC, MEK inhibitors for mucosal melanomas, IDH2 inhibitors for neuroendocrine and SNUC 48 and ONB, 52 and EZH2 inhibitors for SNUC, 48 while DNA repair and FGFR inhibitors may be considered for many of the SNC subtypes. Moreover, several studies on tumor‐infiltrating lymphocytes and aspects of the PD‐L1/PD1 checkpoint have indicated a role for immunotherapy in several sinonasal tumor subtypes 60–62 …”
Section: Adjuvant Immunotherapy and Other Biologic Response Modifiersmentioning
confidence: 99%
“…Another candidate treatment option for PDC is immunotherapy, although few studies have studied immune checkpoint inhibitors in these tumors. Recent immunotherapeutic biomarker studies have reported CD8+ TILs in up to 20% of ONBs, which were associated with a more favorable prognosis [71][72][73]. PD-L1 expression occurred in 14-20% of ONBs.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 expression occurred in 14-20% of ONBs. CD8+ TILs and PD-L1 expression have also been observed in 17% and 33% of SNECs, respectively, and in 33% and 16% of SNUCs, respectively [73]. Other biomarkers include the tumor mutation burden and microsatellite instability, but few data on PDC are available.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis also allows for the identification of molecular targets for modern targeted therapies. Several studies on tumor-infiltrating lymphocytes and aspects of the PD-L1/PD1 checkpoint have indicated a role for immunotherapy in several sinonasal tumor subtypes [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], and we strongly encourage research into the clinical response to treatment with immune checkpoint inhibitors in sinonasal cancers such as recently reported on MMM [ 17 ]. Next-generation sequencing identified recurrent subtype-unique mutations including: APC , CTNNB1 , PIK3CA and KRAS in ITAC, EGFR and CDKN2A in SNSCC, NRAS and NF1 in MMM, IDH2 in SNUC, and ARID1A , SMARCB1 and SMARCA4 in SNEC, SNUC and TCS [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
mentioning
confidence: 88%